Is ECVET fostering the establishment of a European mobility network? : The example of CREDCHEM - Eberhardt, Christiane [Verfasser]; Schlegel, Beatrice [Verfasser] (My University, 2012)
On the basis of the chemical sector the authors illustrate the necessity of promoting international competence. The interests of the European chemical industry are congruent with the efforts made in the European educational policy. Since March 2009, CREDCHEM has been piloting the ECVET instrument, which aims at reducing barriers to mobility. CREDCHEM is a collaboration of VET institutes from Bulgaria (NAVET), the Czech Republic (NUV), Slovakia (SIOV) and Germany (BIBB). Pedagogical Support was provided by the relevant chemical and environmental faculties of the Technical University of Dresden. The main principle for CREDCHEM was that mobility phases in skilled work in the chemical sector can only be achieved in the medium or long run. The following passages describe meticulously the methodological approach which can be described as the conversion from the work task to the learning outcome unit. These units are able to map a complete occupation. Working competence can only be identified in connection with work tasks. Therefore monitoring of increased competence an increased at the end of a learning phase abroad takes place by competence oriented test assignments. Furthermore there is also an assessment form reflecting professional skills, problem solving ability, communication skills and team player skills. There are many indications has so far succeeded in establishing structural approaches which are favorable for the promotion of ECVET aimed at improving transnational mobility even if these three years of project piloting reveal problems that remain open. For example the extent to which dual training partners will be able and open to impart units of learning outcomes within their everyday company routine. It goes without saying that ECVET based mobility requires an appropriate infrastructure. (BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 1.3.3.3 Mobilität; G 1.2.4.1.4 Verarbeitendes Gewerbe; Europäisches Leistungspunktesystem; Berufsbildung; Mobilitätsförderung; Chemische Industrie; Europa